2006
DOI: 10.1148/radiol.2391050221
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Manual and Automatic Section Positioning of Brain MR Images

Abstract: The study protocol was approved by the institutional review board and was in full compliance with HIPAA guidelines. Informed consent was obtained from all patients. The purpose of this study was to prospectively compare intra- and intersubject variability of manual versus automatic magnetic resonance (MR) imaging section prescription. In two examinations, T2-weighted series were acquired with both methods. All intrasubject and three of six intersubject section prescription variances were significantly higher f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 23 publications
2
41
0
Order By: Relevance
“…To our knowledge, MRI with automatic section prescription and scanning has up to now not been evaluated in the same patients pre-and postoperatively, while follow-up MR examinations of glioma patients represent one of the most common routine clinical applications. Compared with manual section prescription, the variation of section planning using automatic planscan alignment in our study population was similar to or smaller than the values that are reported in the literature (2,4).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…To our knowledge, MRI with automatic section prescription and scanning has up to now not been evaluated in the same patients pre-and postoperatively, while follow-up MR examinations of glioma patients represent one of the most common routine clinical applications. Compared with manual section prescription, the variation of section planning using automatic planscan alignment in our study population was similar to or smaller than the values that are reported in the literature (2,4).…”
Section: Discussionsupporting
confidence: 86%
“…holds true for determining the reduction of examination and processing times using ASP; although we could not compare the time frames of manual and automatic scanning directly (except by doubling all of the sequences which is impracticable when examining patients), manual planning of all sequences of a given protocol will take longer in almost all cases than the acquisition of the ASP localizer dataset and subsequent automatic propagation of the ASP planscans, especially when precise alignment is required or if the patient is in an unusual position (2). A quantitative assessment of the variance between ASP planscans and an additional postacquisition registration of the pre-and postoperative images has not been performed, see, for example, Cachier et al (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All scans were 3D sagittal acquisitions with 128 contiguous slices (imaging matrix = 256x192, in-plane resolution = 1mm, and slice thickness = 1.33mm). In each Siemens scan session, the acquisitions were automatically aligned to a standardized anatomical atlas to ensure consistent slice prescription across scans (van der Kouwe et al, 2005;Benner et al, 2006).…”
Section: Mri Data Acquisitionmentioning
confidence: 99%